Pemanfaatan Media Saran dan Kritik Orang Tua Berbasis Web Untuk Meningkatkan Iklim Kemanan Sekolah - Kurniyawan, Deni; Rejokirono, Rejokirono; Mulyono, Rahmat (Media Manajemen Pendidikan, 2025)
This research aims to examine and investigate the use of online suggestions and critiques from parents in order to enhance safe environment conditions; also, it provides insights on how effective online platforms are at promoting open communication between schools and parents with reference to safety issues at SMP Negeri 11 Magelang. By employing qualitative analysis through qualitative research methodology that entails a case study design approach, the study was done. The main point was on whether parents use web-based media when offering suggestions or making criticisms. Based on data analysis conducted, the platform was found to be useful in handling suggestions and criticisms made by parents. It was noted by respondents that this platform encouraged more involvement by parents into matters concerning school safety. Among these respondents who were parents, 80% indicated they were satisfied while 85% were learners.